Elastic analysis of a half-plane containing an inclusion and a void using a mixed volume and boundary integral equation method - Lee, J.K.; Mal, A. (Engineering analysis with boundary elements, 2011)
A mixed volume and boundary integral equation method is used to calculate the plane elastostatic field in an isotropic elastic half-plane containing an isotropic or anisotropic inclusion and a void subject to remote loading parallel to a traction-free boundary. A detailed analysis of the stress field is carried out for three different geometries of the problem. It is demonstrated that the method is very accurate and effective for investigating local stresses in an isotropic elastic half-plane containing multiple isotropic or anisotropic inclusions and multiple voids.